A new development paradigm: employment, entitlement and empowerment - Virmani, Arvind (2002)
At the beginning of the 21st century there is the need for a new development paradigm that recognises that `government failure' is a much more important problem than `market failure'. `Privatisation' of government services by its employees and government's monopoly of power are the real problems today. The new paradigm must be based on a clear and non-ideological recognition of the strengths and the weakness of the state and the people. A democratic society has enormous potential for entrepreneurship, innovation and creative development. The people, their diverse forms of activity and association such as companies, cooperatives, societies, trusts and other NGOs must be allowed and encouraged to play their due role. The state must focus on what only it can do best and shed all activities that the people can do as well or better. The heavy hand of government in the form of incentive-distorting laws, rules, regulations, procedures and red tape have also corrupted industry and business and other organised interest groups. These must be removed so as to release the energy of the people. The state should confine itself to managing the economy so as to accelerate employment and income growth in a self-sustaining manner, ensure that all citizens receive their basic entitlements of basic public goods and services and empower the poor so that they have equal rights (and responsibilities) with the better off citizens. -Reproduced.
Keywords: Women; Employment